PPARγ is dispensable for clear cell renal cell carcinoma progression - Danielle J. Sanchez; David J. Steger; Nicolas Skuli; Ankita Bansal; M. Celeste Simon (Elsevier, 2018)
Objective: Clear cell renal cell carcinoma (ccRCC) is a subtype of kidney cancer defined by robust lipid accumulation, which prior studies have indicated plays an important role in tumor progression. We hypothesized that the peroxisome proliferator-activated receptor gamma (PPARγ), detected in both ccRCC tumors and cell lines, promotes lipid storage in ccRCC and contributes to tumorigenesis in this setting. PPARγ transcriptionally regulates a number of genes involved in lipid and glucose metabolism in adipocytes, yet its role in ccRCC has not been described. The objective of this study was to elucidate endogenous PPARγ function in ccRCC cells. Methods and results: Using chromatin immunoprecipitation followed by deep sequencing (ChIP-seq), we found that PPARγ and its heterodimer RXR occupy the canonical DR1 PPAR binding motif at approximately 1000 locations throughout the genome that can be subdivided into adipose-shared and ccRCC-specific sites. CRISPR-Cas9 mediated, loss-of-function studies determined that PPARγ is dispensable for viability, proliferation, and migration of ccRCC cells in vitro and in vivo. Also, surprisingly, PPARγ deletion had little effect on the robust lipid accumulation that typifies the "clear cell" phenotype of kidney cancer. Conclusion: Our results suggest that PPARγ plays neither a tumor suppressive nor oncogenic role in advanced ccRCC, and thus single-agent therapeutics targeting PPARγ are unlikely to be effective for the treatment of this disease. The unique cistrome of PPARγ in ccRCC cells demonstrates the importance of cell type in determining the functions of PPARγ. Keywords: Nuclear receptors, PPARγ, Kidney cancer, Cancer metabolism, Lipid metabolism